Food Consumption Diversification Using Food Desirable Pattern Approach in Nutritionally Vulnerable Regencies - Tejasari . (Media Gizi dan Keluarga, 2003)
To divers& foods is an important aspect of food consumption since certain food doesn't supply all nutrients completely. Adequate and diverse food cot~sumption will guarantee thejirIIfiIlntent of variabilty of n~rtrieritsn eeded for organs and physiological systenl firnctioning normally and balance. This slue was done in nutritionally vulnerable regencieswere determined based on percentage of energy fulfillment toward Recommended Dietary Allowances (RDA) derived from its communi~fo od con~?rmptionA. bmit 12 rnrtritionallyl~rrlt~erahlkee can7atati cozititie.s, which determined hased on preschooler nrrtritional statrrs wing weight for age (wt,%e) indicator collectedfrom Commrinity Health ('entre (Ptrske.\ma.s) and Health Serl1ice.s lltiit (/lo.\y~~nhrp)o oling data. hbod coti.stmtptiot1 divrr.s~fica/ionzr sing,food de.sirable pattern approach was evaluated hased on qualitative h t a of family .food cotntrn~ptiotiw, hich calc~rIated,fiomth eir.focd cotnun~ptiotdi ata derivedfrom 24 hours l+bod Recall- method for 3 days. The results showed that food consumption diversrfication in those districts were 1014~ sitice the average q~ralitatived ata reached only 56 compared to the national food desirable pattern. Qtralitive score of family '.s food constrmption in coastal mrtritionally ~~rrlnerahaler ea was 53, lower than those it1 ~irhatal rea hy 54 arid agrictrltirral area by 56 or marginal area by 60. Energy contribrrtion from food consumed did not reach the energy composition from nine food grorips recommended hy national focd desirable pattern. Rased on this national standard, except for quality value of nut group, the nutritionally vulnerable area have to increase the highest q~ralityv alue by 17from cereals in marginal area, by 3.from tuber root in coastal area, by 2 I from animal food in coastal area, by 8from oil and fat group in rrrhan area, by 2from oib frrrit and seed, atidfrom sugar, and 7@om vegetuh1e.s and fruit in rrrban area. Statistically, family S socio economy and demographyc charracteristics in thoseareas did riot infliretice the qtrali/y valtre of ,familyS .food cotatmlption sig~i~ficanti). (bn~)erselyi,n marginal areas, qualitative data of family '.s food cota~imptionw ere inji'uencedhy the type qfjoh qf the head,family and housewives signrficantlq! Key Words : Diversijikasi Konsumsi Pangan, Pola Pangan Harapan , Rawan GiLi, Klasifikasi Fungsi (;eogrnfis